Het pluriversum van Lucien Goethals - Dierickx, Jelle (Leuven MATRIX, 2016)
Lucien Goethals was one of the most influential composers of the Belgian music scene in the second half of the 20th century. Born in Ghent, he studied at the Dima Conservatory of Buenos Aires and at the Royal Conservatory of Ghent. He was closely related to the IPEM (Institute for Psychoacoustics and Electronic Music in Ghent) where he immersed himself in the study of electronic music and innovative musical techniques. He developed a personal language in which electronics and acoustic instruments were closely intertwined. Lucien Goethals passed away in 2006. Forming a part of the European avant-garde of the time, his music evolved from a modernist language into an organic and colorful style surpassing the apparent contradictions between tradition (of a.o. the Franco-Flemish polyphonists) and innovation.
Keywords: Goethals, Lucien -- 1931-2006; IPEM (Ghent, Belgium); 20th Century (1901-2000); Composer; Avant-garde; Serialism; Belgium